1999
DOI: 10.1038/sj.bjc.6690551
|View full text |Cite
|
Sign up to set email alerts
|

The role of human melanoma cell ICAM-1 expression on lymphokine activated killer cell-mediated lysis, and the effect of retinoic acid

Abstract: Intercellular adhesion molecule (ICAM-1) exists as a membrane-associated form (mICAM-1) on the surface of tumour cells as well as a soluble form (sICAM-1). This study analyses the ability of all- trans retinoic acid (RA) to alter both sICAM and mICAM-1 expression in C8161 and Hs294T human melanoma cell lines and investigates the involvement of ICAM-1 in the interaction between tumour and lymphokine-activated killer (LAK) cells using the Cr-51 release assay. Our data showed that 4-day pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Retinoic acid treatment rendered hepatoma cell more susceptible to NK cells and also augmented the ability of hepatoma cells to induce IFNγ production from NK cells. It was previously reported that retinoic acid can modulate expression of HLA Class I, ICAM‐1 and CD95 in certain cell types and thereby affect their susceptibility to effector cell‐mediated cytolysis and apoptotic cell death 26, 28. This is not likely to be the case with hepatoma cells, however, because ATRA treatment did not affect the expression of these molecules on Huh7, HepG2 and Hep3B hepatoma cells (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Retinoic acid treatment rendered hepatoma cell more susceptible to NK cells and also augmented the ability of hepatoma cells to induce IFNγ production from NK cells. It was previously reported that retinoic acid can modulate expression of HLA Class I, ICAM‐1 and CD95 in certain cell types and thereby affect their susceptibility to effector cell‐mediated cytolysis and apoptotic cell death 26, 28. This is not likely to be the case with hepatoma cells, however, because ATRA treatment did not affect the expression of these molecules on Huh7, HepG2 and Hep3B hepatoma cells (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…metastasis. 10 This somewhat conflicting statement is explained by the existence of sICAM-1 that can interact with LFA-1 on the lymphocyte and block the lymphocyte from interacting with, and lysing the tumor cells. 11 -14 Nude mouse models have previously shown melanoma cells to be a source of sICAM-1, a finding supported by the observation that melanoma cell lines secrete sICAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other groups were not able to confirm these findings. 10 However, the general opinion is that, in the in 6i6o situation, sICAM-1 may exist bound to other proteins or as a multimeric form which may have a great potential to bind to LFA-1 sites on the lymphocyte, thus contributing to tumor cell evasion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations